The role of local government in the economic development of the urban district of Krasnogorsk ("Journal "U". Economy. Management. Finance.", 2024)
This article examines the role of local government in the economic development of the Krasnogorsk urban district. The main programs and initiatives, aimed at stimulating economic growth, creating jobs and attracting investments are being investigated. Special attention is paid to the analysis of strategies that have been successfully implemented by the city district administration, as well as current challenges and ways to overcome them. The article presents examples of best practices and recommendations for the further development of municipal management to achieve sustainable economic growth and improve the quality of life of the population.
Keywords: local government; economic development; Krasnogorsk; investments; jobs; programs; initiatives